Kemampuan Kolaborasi Wirausaha Mahasiswa Melalui Model Project Based Learning (PJBL) Menggunakan Platform babari.id Pada Sub CPMK Merencanakan Usaha Dengan Sistem Maklun - Disman; Maula, Afief Maula Novendra; Ahman, Eeng (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This research aims to determine the increase in students' collaboration skills through a project based learning model using the babari.id platform in Sub CPMK planning businesses using the maklun system. The research method used is experimentation with a pre-experimental design in the form of a one-shot case study. The population in this study were 5th semester students who were taking entrepreneurship courses at the Economic Education Study Program, FKIP, Pasundan University. The instruments used were initial and final observation sheets. Data analysis used descriptive statistics and inferential statistics, data processing used IBM SPSS Statistics 26. The research results showed that students' entrepreneurial collaboration ability through PJBL using the babari.id platform before treatment was 2.8, including quite good criteria, and after treatment it was 4. 2 is included in the very good criteria, with an average increase of 1.4. The T sig (2-tailed) test results were 0.00 < 0.05. So the hypothesis h0 is rejected while ha is accepted. In this way, there is an increase in students' entrepreneurial collaboration skills through a project based learning model using the babari.id platform in the CPMK sub-planning business using the Maklun system.